Literary visions - Dorn, Fran; Davis, Scott Hilton; Maryland Public Television; Corporation for College Television; Annenberg/CPB Collection (S. Burlington, VT : Annenberg/CPB Collection, 1992)
Examines three major genres of literature, short fiction, poetry and drama, and discusses literary elements such as character, plot, symbolism, and voice.
A 26-part telecourse discussing literature and authorship, presented in two 30-minute lessons per videocassette in 5 parts.
1. First sight: an introduction to literature -- 2. Ways of seeing: responding to literature -- 3. A personal view: the art of the essay -- 4. Reflected worlds: the elements of short fiction -- 5. The story's blueprint: plot and structure in short fiction -- 6. Telling their tales: character in short fiction -- 7. In that time and place: setting and character in short fiction -- 8. The author's voice: tone and style in short fiction -- 9. Suggested meanings: symbolism and allegory in short fiction -- 10. The sum of its parts: theme in short fiction -- 11. The sacred words: the elements of poetry --12. A sense of place: setting and character in poetry --13. Tools of the trade: words and images in poetry -- 14. Seeing anew: rhetorical figures in poetry -- 15. An echo to the sense: prosody and form in poetry -- 16. Distant voices: myth, symbolism, and allusion in poetry -- 17. Artful resonance: theme in poetry -- 18. Playing the part: character and actors in drama -- 19. Patterns of action: plot and conflict drama -- 20. Perspectives on illusion: setting and staging in drama -- 21. The vision quest: myth and symbolism in drama -- 22. A frame for meaning: theme in drama. 23. Casting long shadows: the power of literature -- 24. Continuing vision: the uses of literature.
DVD
Closed-captioned for the hearing impaired.
24 parts on 6 videodiscs, each part is 30 minutes long.
Hosted by Fran Dorn.
Secondary through college level students.
No Masters.
Keywords: Literature -- Appreciation; Authorship; Style, Literary; Video recordings for the hearing impaired